103k views
1 vote
12) Complete the table for m(x) = 5 - X. Show your work in the space below.m(x)3.-8.6

User Jyriand
by
5.2k points

1 Answer

4 votes

Here we have:

m(x) = 5 - x

which is: y = m(x) = 5 -x

To solve this, substitute each value given for x in the equation.

12) Complete the table for m(x) = 5 - X. Show your work in the space below.m(x)3.-8.6-example-1
User Scrfix
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.